2015
DOI: 10.1016/j.cortex.2015.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Transport for language south of the Sylvian fissure: The routes and history of the main tracts and stations in the ventral language network

Abstract: It is now ten years since a 'ventral language pathway' was demonstrated in vivo in the human brain. In the intervening decade, this result has been replicated and expanded to include multiple possible pathways and functions. Despite this considerable level of research interest, age-old debates regarding the origin, course, termination and, indeed, the very existence of the tracts identified still remain. The current review examines four major tracts associated with the ventral 'semantic' language network, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 89 publications
4
52
1
Order By: Relevance
“…This provides new insight into the strong modulatory potential of cTBS. Probabilistic fiber tracking revealed that this effect was most probably mediated via anatomical long-distance connections that are part of the ventral association fibre system that was previously associated with semantic processing (Bajada et al, 2015). …”
Section: Discussionmentioning
confidence: 92%
“…This provides new insight into the strong modulatory potential of cTBS. Probabilistic fiber tracking revealed that this effect was most probably mediated via anatomical long-distance connections that are part of the ventral association fibre system that was previously associated with semantic processing (Bajada et al, 2015). …”
Section: Discussionmentioning
confidence: 92%
“…Diffusion-weighted images were acquired in 24 healthy volunteers (11 females; mean age 25.9, range 19–47) without any record of neurological or psychiatric disorders, a dataset described previously and utilized for various tractography-related explorations (Cloutman et al 2012; Binney et al 2012; Jung et al 2016; Bajada et al 2015, 2017). All participants were right-handed, as assessed by the Edinburgh Handedness Inventory (Oldfield 1971).…”
Section: Methodsmentioning
confidence: 99%
“…In humans and primates, the ATL region is strongly connected to a variety of cortical regions, including primary sensory cortices, posterior temporal and occipital cortex, medial structures (limbic cortices, hippocampal systems, and olfactory systems), and frontal systems that play roles in executive function and social cognition/valence . The pattern of long‐range, major white matter tracts also emphasizes the hub‐like connectivity of the ATL region, including convergence of the inferior longitudinal fasiculus (from posterior vOT and occipital areas), the middle longitudinal fasciculus (from inferior parietal and primary auditory regions), the uncinate fasciculus, and perhaps branches of the inferior frontal–occipital fasciculus (from various orbitofrontal, lateral frontal, and limbic regions).…”
Section: Role Of the Bilateral Versus Unilateral Atls In Conceptual Kmentioning
confidence: 99%